A nationwide study on prevalence and factors associated with dynapenia in older adults: ELSI-Brazil - Viviane Santos Borges; Maria Fernanda Furtado Lima-Costa; Fabíola Bof de Andrade (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
This study aimed to assess the prevalence and factors associated with dynapenia in a nationally representative sample of Brazilians aged 50 years and older. A cross-sectional study was performed with baseline data from the Brazilian Longitudinal Study of Aging (ELSI-Brazil). Dynapenia was defined as low muscle strength (< 27kg for men and < 16kg for women). Explanatory variables were sociodemographic characteristics, health conditions, health behaviors and physical performance. Analyses were based on multivariate logistic regression and population attributable fractions. Among the 8,396 participants, the prevalence of dynapenia was 17.2% (16.6% among men and 17.7% among women); for those aged 65 years and older, the prevalence was 28.2% (29.1% and 27.5% among men and women, respectively). Dynapenia was positively associated with age, low gait speed, limitations in performing two or more basic daily activities, falls and self-reported chronic diseases; and negatively associated with education level, physical activity and body mass index (overweight/obese, OR = 0.26). Prevalence of dynapenia is high in Brazilian older adults. Educational skills and physical activity improvement present greater potential to reduce dynapenia in this population.